Adjuvantes em pulverizações de fungicidas na cultura do trigo - Souza, Bruno José Rodrigues De; Perez, Pedro Henrique; Bauer, Fernando César; Raetano, Carlos Gilberto [UNESP]; Weirich Neto, Pedro Henrique; Garcia, Luiz Cláudio (Universidade Federal de Santa Maria, 2014)
The foliar diseases and spike can markedly reduce the yield of wheat. Despite prevailing chemical control in the management of disease, studies with adjuvants to improve the performance of fungicides are still incipient. The aim of this study was to evaluate the effect of adding adjuvants to chemical fungicides to control leaf diseases and spike, as well as on the yield of wheat crop. The experimental design was a randomized block design with 05 treatments: control (no fungicide application in the shoot); fungicides only in shoots; fungicides + adjuvant base of orange essential oil; fungicides + lecithin-based adjuvant and acid propionic; fungicides + adjuvant base of orange essential oil+ lecithin-based adjuvant and acid propionic, in 04 repetitions. The treatments were applied during the harvests of 2011 (04 fungicide applications) and 2012 (05 fungicide applications).The variables assessed were incidence and severity of diseases, yield components and economic return. In the 2011 harvest the addition of adjuvants in the spray syrup affect the performance of the fungicides the, the number of grains per spike, yield and economic return with the Supera(c) variety. In 2012 the addition of adjuvant to the fungicide influenced the severity of disease, especially using Tbio Itaipu(c) variety. The higher the investment in wheat and increase the number of fungicide application, the smaller the impact of the adjuvant in the spray technology.

As doenças foliares e da espiga podem reduzir acentuadamente a produtividade da cultura do trigo. Apesar de prevalecer o controle químico no manejo das doenças, os estudos com adjuvantes para melhoria do desempenho de fungicidas ainda são incipientes. O objetivo deste trabalho foi avaliar o efeito da adição de adjuvantes aos fungicidas no controle químico de doenças foliares e da espiga, bem como sobre os componentes de rendimento da cultura do trigo. O delineamento experimental foi o de blocos casualizados, com 05 tratamentos: testemunha (sem aplicação de fungicidas na parte aérea); somente fungicidas na parte aérea; fungicidas + adjuvante a base de óleo essencial de laranja; fungicidas + adjuvante a base de lecitina e ácido propiônico; fungicidas + adjuvantes a base de óleo essencial de laranja+ adjuvante a base de lecitina e ácido propiônico, em 04 repetições. Os tratamentos foram aplicados nas safras agrícolas de 2011 (04 aplicações de fungicidas) e 2012 (05 aplicações de fungicidas). As variáveis avaliadas foram incidência e severidade de doenças, componentes de rendimento e retorno econômico. Na safra de 2011, a adição de adjuvantes à calda de pulverização interferiu no desempenho dos fungicidas e afetou significativamente a severidade de doenças, o número de grãos por espigas, produtividade e o retorno econômico com a cultivar Supera(r). Em 2012, a adição de adjuvante à calda fungicida também influenciou o desempenho dos fungicidas; sendo de forma significativa a severidade de doenças na cv. Tbio Itaipu(r). Quanto maior o investimento na cultura do trigo e elevação do número de aplicação de fungicidas, menor o impacto do adjuvante na tecnologia de aplicação.
Adjuvants for spraying of fungicides in wheat
Keywords: doenças; pulverizador terrestre de barra; Triticum aestivum; disease; spray boom; Triticum aestivum